Determining the Difference in the Effectiveness of Cognitive Behavioral Therapy and Schema Therapy on Emotional Inhibition in Adolescents with High-Risk Behaviors - Ghafari Moghadam, Fahimeh; Dehghani-Arani, Fateme; Zarghami, Elham (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to determine the difference in the effectiveness of cognitive behavioral therapy and schema therapy on emotional inhibition in adolescents with high-risk behaviors. This applied study employed a quasi-experimental design with a pretest–posttest format including a control group and a two-month follow-up period. The statistical population consisted of adolescents with high-risk behaviors referred to counseling centers affiliated with the Department of Education in Karaj in 2025. Using purposive sampling, 45 participants who met the inclusion criteria were selected and randomly assigned into three groups: cognitive behavioral therapy (n = 15), schema therapy (n = 15), and control (n = 15). The experimental groups received eight sessions of structured interventions based on standardized therapeutic protocols, while the control group remained on a waiting list. Data were collected using the Emotional Inhibition Scale (EIS). Data analysis was conducted using SPSS-26 software at both descriptive and inferential levels, including repeated measures analysis of variance (ANOVA) and Bonferroni post hoc tests after verifying statistical assumptions. The results indicated that the main effect of group on emotional inhibition was not statistically significant (F = 0.62, p = 0.544), whereas the main effect of time was significant (F = 7.27, p = 0.008), indicating changes across measurement stages. Additionally, the interaction effect between time and group was significant (F = 4.59, p = 0.042), suggesting differential changes across groups over time. Bonferroni post hoc comparisons revealed that schema therapy significantly reduced emotional inhibition compared to the control group at posttest (p = 0.016), while cognitive behavioral therapy did not show a significant difference compared to the control group (p = 0.664). Within-group comparisons demonstrated significant improvements in the schema therapy group from pretest to posttest (p = 0.022) and follow-up (p = 0.034), whereas no significant changes were observed in the cognitive behavioral therapy and control groups (p > 0.05). The findings suggest that schema therapy is more effective than cognitive behavioral therapy in reducing emotional inhibition among adolescents with high-risk behaviors, with effects that are sustained over time, highlighting the importance of targeting deep cognitive-emotional structures in therapeutic interventions.